Respon Kumbang Tribolium castaneum Herbst terhadap Umpan Berbasis Semiokimia - Rostaman Rostaman; R. C. Hidayat Soesilohadi; Rurini Retnowati (Jurnal Perlindungan Tanaman Indonesia, 2003)
Monitoring of the red flour beetle (Tribolium castaneum Herbst) population by using semiochemical. based bait is important for supporting integrated pest management program. The baits were formulated succesfully using wheat bran as carrier and vegetable oils such as corn oil, soybean oil and palm oil as kairomone, and 4,8 dimethyl decanal. (DMD) as aggregation pheromone. The beetles responded to all baits both in laboratory and warehouse. The level of attractancy on bait loaded DMD is higher than others. Therefore loading of DMD is obligatory.